PENERAPAN METODE TOPSIS DALAM PENENTUAN DOSEN TERBAIK - Gunawan Wibisono; Arif Amrulloh; EIH Ujianto (ILKOM Jurnal Ilmiah, 2019)
Appreciation for the performance of a worker is very important in the aim of valuing his efforts for the institution. In the world of education, especially universities, lecturers are one of the main components in building quality and quantity. The good quality of lecturers should also provide good quality graduates, while the quantity or number of lecturers will affect the number of students in the college. In the aim of building the quality of lecturers, the award in the form of ranking the best lecturers can be an alternative trigger for quality improvement. Decision support systems (DSS) can be a tool that helps rank the best lecturers, of course with criteria to produce ranking alternatives. The length of work, achievements and tridharma (teaching, research, and consecration) of higher education is used as a criterion to obtain the best alternative rank of lecturers from the number of lecturers as many as 20 people. Lecturer data is taken from the telecommunication engineering study program Institut Teknologi Telkom Purwokerto (ITTP). The TOPSIS method was chosen in this multicriteria DSS, the result was 6 selected lecturers to be the best alternative lecturers and from these results it turned out that the most influential was the number of research and teaching rankings, while the duration of work did not affect much.